International trade and conflict relationship - Hamid, Zarinah (Serials Publications (New Delhi, India), 2007)
This article investigates if the trade-conflict theory can be applied to the world in current times. Trade, conflict and peace data of ten countries from 2000 to 2004 have been used to explain the trade and conflict relationship. The ten countries are as follows; USA, UK, Germany, China, Israel, India, Pakistan, Lebanon, Syria and The Russian Federation. An index which measures the amount of conflict is regressed upon a set of explanatory variables. The findings provide an indication that countries with greater trade dependency engage in less conflict.